FUNDUSZ POMOCY POKRZYWDZONYM ORAZ POMOCY POSTPENITENCJARNEJ PO NAJNOWSZYCH ZMIANACH - Bieńkowska, Ewa (Zeszyty Prawnicze, 2016)
Crime Victims and the Polish Post-penitentiary Fund Following the Latest Changes Summary This paper presents a critical analysis of the provisions in force relating to the Polish Crime Victims and Post-Penitentiary Fund (Fundusz Pomocy Pokrzywdzonym oraz Pomocy Postpenitencjarnej). Recently there have been important changes in these provisions, particularly on the grounds of the Act of 28 November 2014 on the protection of and assistance to victims of crime and witnesses (Ustawa z dnia 28 listopada 2014 r. o ochronie i pomocy dla pokrzywdzonego i świadka) and the associated executive regulations of 29 September 2015 introduced by the Ministry of Justice. The scope of the Fund’s tasks has been extended to cover legal and psychological assistance to witnesses and their next-ofkin, and the rules for the financing of the Fund’s activities have been modified. Most of these changes concern the provisions relating to victims, who are now in a worse situation than before the Act came into force, which runs counter to the main purpose of Directive 2012/29/EU of the European Parliament and of the Council of 25 October 2012 establishing minimum standards on the rights, support and protection of victims of crime.